Resource conservation technologies for enhancing productivity, economics and resource use efficiency under soybean-wheat cropping system - Vishwakarma, A K; Lakaria, B L; Shirale, A O; Kamble, A L; Singh, R K; Wanjari, R H; Singh, A B; Shirale, A O; Bharti, K; Sahu, Asha; C, Shinogi K; Biswas, A K; et al. (Indian Farming, 2021)
The study was conducted in a cluster of four villages namely Khamkheda, Bherupur, Kanchbavali and Kalyanpur located in two panchayats viz. Kham Kheda and Golkhedi respectively in the Huzur tehsil of Phanda block in Bhopal district. Results show that there is an overall reduction in the cost of cultivation of soybean by 15% and 10% in wheat cultivation under conservation agriculture. Results revealed that the grain yield increased by 8.67% and 6.55% as compared to conventional tillage for soybean and wheat respectively. The net profit in conservation agriculture was 40% and 25% higher as compared to conventional system in case of soybean and wheat respectively. The B: C ratio was also higher under CA (2.30 and 3.08) as compared to conventional method (1.79 and 2.50). The system productivity increased by 7.36% (wheat equivalent yield), under conservation agriculture as compared to conventional tillage and water productivity of the system increased from 1.08 kg/m3 in conventional tillage system to 1.34 kg/m3 under conservation agriculture with balanced fertilizer application, indicating a gain of 24.67% in water productivity under conservation agriculture as compared to conventional agriculture. The overall diesel consumption was reduced from 112 lit/ha under conventional agriculture to 40 lit/ha under conservation agriculture, indicating an overall reduction of 64.3% in diesel requirement for crop establishment. The overall energy equivalence of conventional system is 6306.72 MJ/ha against only 2252.40 MJ/ha under conservation agriculture. Total water requirement is reduced by 25.3% due to saving of an irrigation and less time required for irrigating the field which resulted in savings of power requirement under conservation agriculture.